PREJUDICE REDUCTION DALAM AJARAN AGAMA-AGAMA - Erham Budi Wiranto (LP2M IAIN Palangka Raya, 2020)
Religion was regarded as a source of prejudice against others who are different, even a source of hatred. In fact, as complex teachings, religions had opposite role, reducing prejudice. This study attempted to find religious values that can be useful for prejudice reduction. With a qualitative method, religious values reducing prejudice were explored from five religions, namely Hinduism, Buddhism, Catholicism, Christianity and Islam. Data were collected through studying religious texts, both from the main sources and the works of religious leaders. The finding found that all religions had fundamental values that could reduce prejudice. These values generally were in the form of respect for diversity, prohibition of acting unfairly, and prohibiting acts of violence. This finding was expected to refute the assumption that religion was a source of prejudice, hatred and horizontal conflict.